2020
DOI: 10.1002/adom.202000690
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Spontaneous Emission and Random Lasing in MAPbBr3 Halide Perovskite Single Crystals

Abstract: Halide perovskites are a promising optical gain medium with high tunability and simple solution synthesis. In this study, two gain regimes, namely, amplified spontaneous emission and random lasing, are demonstrated in the same MAPbBr3 halide perovskite single crystal. For this, photoluminescence is measured at a temperature of 4 K with pulsed femtosecond pumping by UV light with an 80 MHz repetition rate. Random lasing is observed in areas of the sample where a random resonator is formed due to cracks and crys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…Nevertheless, this tail state plays an important role in lasing phenomenon, as it was demonstrated that the laser gain spectral region is located well below the BE resonance. [5] In this study, we demonstrate that the PL from defect-related states can be revealed by the careful and precise selection of the excitation energy (E ex ). We use the micro-photoluminescence excitation (PLE) spectroscopy to study the MAPbI 3 single crystals at 5 K temperature.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Nevertheless, this tail state plays an important role in lasing phenomenon, as it was demonstrated that the laser gain spectral region is located well below the BE resonance. [5] In this study, we demonstrate that the PL from defect-related states can be revealed by the careful and precise selection of the excitation energy (E ex ). We use the micro-photoluminescence excitation (PLE) spectroscopy to study the MAPbI 3 single crystals at 5 K temperature.…”
mentioning
confidence: 73%
“…Nevertheless, this tail state plays an important role in lasing phenomenon, as it was demonstrated that the laser gain spectral region is located well below the BE resonance. [ 5 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] Nevertheless, controlling the emission wavelength of random lasers is still challenging due to the absence of optical cavity, which limits their applications in some fields such as medical detection, [ 13 ] photonic crystals, [ 14,15 ] and high‐precision sensors. [ 16,17 ] Therefore, emission characteristics of random lasers, especially the control strategies of the emission wavelengths, have attracted increasing attention, so far, various optical structures have been reported, including liquid crystals, [ 18 ] quantum dots, [ 19,20 ] graphene/semiconductor heterostructures, [ 21 ] polymer films, [ 22 ] disordered photonic crystal platform, [ 23 ] perovskite single crystals, [ 24 ] fibers, [ 5,25,26 ] and fiber gratings. [ 27 ] For example, Perumbiavil et al.…”
Section: Introductionmentioning
confidence: 99%
“…The green-emitting CH 3 NH 3 PbBr 3 (MAPbBr 3 ) is one of the most popular HOIP materials for investigations on lasing devices [18][19][20] because of its high emission efficiency, excellent stability, and easy synthesizing and processing advantages. MAPbBr 3 is a directbandgap material with a bandgap energy of about 2.3 eV, which may be excited to produce green light emission.…”
Section: Introductionmentioning
confidence: 99%